STANDAR PELAKSANAAN AKAD MUSYARAKAH DAN PERLAKUAN AKUNTANSI MUSYARAKAH BERDASARKAN PSAK 106 PADA PERBANKAN SYARIAH - Balya Rifqi Abd.Wahid; Triya Oftafiana; Binti Nur Aisyah (RIBHUNA : Jurnal Keuangan dan Perbankan Syariah, 2024)
Abstract Efforts made by Islamic financial institutions in order to eliminate riba are by applying sharia principles and profit-sharing systems. Some of the financing that applies the principle of profit sharing are the contracts of mudharabah, musharakah, muzara'ah and musaqah. The commonly used ones are mudharabah and musharakah. The relationship between Islamic banks and customers in musharakah is a partnership. It is important for Islamic banking to ensure the implementation of contracts in accordance with the standards so that no party is harmed and with Islamic sharia principles. By conducting literature research from various literature, this article aims to present various theories, rules and principles for musharakah. It then explains about the definition of musharakah, the underlying sharia foundation, basis and requirements and types of musharakah. It also explains about the standards of implementation, supervision and risk management of musharakah. Finally, it depicts the accounting treatment of musharakah based on PSAK 106. Keywords: Musyarakah Agreement, Definition of Musyarakah Agreement, Standard of Musyarakah Agreement, Accounting Treatment of Musyarakah Agreement.